A new species of Phyllanthus L. (Phyllanthaceae) with phylloclades from Minas Gerais, Brazil - Orlandini, Priscila; Cordeiro, Inês; Campos-Rocha, Antonio; Souza, Vinicius Castro (Phytotaxa, 2020)
We described a new species of Phyllanthus currently known from a single fragment of Ombrophilous Dense Forest in the Jequitinhonha Valley, Minas Gerais State, Brazil. Phyllanthus pedicellatus is the second species of the genus with phylloclades found in the Atlantic Forest domain, once mostly Brazilian Phyllanthus with these kinds of specialized branches grow in open vegetation as “campos rupestres” and cerrado. The name is a reference to its remarkable pedicels of pistillate flowers. We present illustrations and photographs of the new species in its habitat, comments on its relationships to other Brazilian Phyllanthus, and its conservation status.